Hydrogen bonding in trivinyl monomers: implications for inclusion complexation and polymerization - Satav, Sunita S.; Karmalkar, Rohini N.; Kulkarni, Mohan G.; Mulpuri, Nagaraju; Sastry, G. Narahari (Macromolecules, 2007)
Trimethylolpropane trimethacrylate (TMPTMA) formed a 1:2 inclusion complex (IC) with beta-cyclodextrin (beta-CD). Polymerization of the complex resulted in a soluble, linear polymer containing two pendant unsaturations per repeat unit since the methacryloyl groups included in the beta-CD cavity did not react with the growing radical chain. Trimethylolpropane triacrylate (TMPTA) formed a 1:1 complex with beta-CD. Yet a soluble polymer containing two pendant unsaturations per repeat unit was obtained. Computational analysis confirmed that in TMPTA hydrogen bonding between C-H center dot center dot center dot O=C brings two acryloyl groups in close vicinity of one another. As a result, both acryloyl groups were included in the same beta-CD cavity. Trimethylolpropane diacrylate 4-vinylbenzoate (TMPDAVB) once again formed 1:2 IC as a result of disruption of hydrogen bonds between two acryloyl groups. The study highlights that an understanding of the composition of the IC is more important than its stoichiometry alone.